x = 2y + 1
x^2 = (2y + 1)(2y + 1) = 4y^2 + 4y + 1
x^2 + y^2 = 29, substitute for x^2 above:
(4y^2 + 4y + 1) + y^2 = 29
5y^2 + 4y + 1 = 29
5y^2 + 4y - 28 = 0
y = (-4 +- sqrt(16-4(5)(28)) / 10
y = (-4 +- sqrt( 16 + 560)) /10
y = (-4 +- 24) / 10
y = -28/10, 20/10 = -14/5, 2
Hope this helps! :)
2007-11-21 10:38:54
·
answer #1
·
answered by disposable_hero_too 6
·
0⤊
0⤋
From the first equation:
x = 2y+1
Replacing x into the second one:
(2y+1)² + y² = 5 y² + 4y + 1 = 29
or
5 y² + 4y - 28 = 0
Then
y = [-4 ± â(16 + 4*5*28)] / (2*5) =
= [-4 ± 24] / 10 = [-2 ± 12] / 5
y1 = 2, y2=-14/5
x1= 5, x2 =-23/5
2007-11-21 18:49:21
·
answer #2
·
answered by GusBsAs 6
·
0⤊
0⤋
solving the first equation for x : x = 2y + 1 and substitute for x in the other equation
(2y + 1)^2 + y^2 = 29
4y^2 + 4y + 1 + y^2 = 29
5y^2 + 4y - 28 = 0
(5y + 14)(y - 2) = 0
y = -14/5 or y = 2
then x = 2y + 1 gives x = -23/5 when y = -14/5
and x = 5 when y = 2
(-23/5, -14,5) and (5,2)
No idea what AS level C1 is....so hope this helped
2007-11-21 18:42:03
·
answer #3
·
answered by Linda K 5
·
0⤊
0⤋
x-2y=1 ---> x = 2y +1
x^2+y^2=29
(2y +1)^2 +y^2 -29 =0
4y^2 +1 +4y +y^2 -29 =0
5y^2 +4y -28 =0
D = 16 +4(28)(5) =576 = 24^2
y1 = (-4 -24)/10 = -28/10 = -14/5
y2 = (-4 +24)/10 = 2
x = 2y +1
x1 = 2(-14/5) +1 = -28/5 +1 = -23/5
x2 = 2(2) +1 =5
Solutions are :
x = -23/5 and y = -14/5
or
x = 5 and y =2
2007-11-21 18:38:51
·
answer #4
·
answered by Any day 6
·
0⤊
0⤋
I get two rational numbers! Using the quadratic formula, I got 576 under the radical. This means it factors. First, let's make sure we agree on the quadratic:
substituting 1+2y for the x:
(1+2y)^2 + y^2 = 29
1 + 4y + 4y^2 + y^2 = 29
5y^2 + 4y - 28 = 0
(5y + 14)(y - 2) = 0
So, y = 14/5, or y = 2
hope this helps!
2007-11-21 18:38:15
·
answer #5
·
answered by Marley K 7
·
1⤊
1⤋
(2y+1)^2 + y^2 = 29
4y^2 + 4y + 1 + y^2 = 29
5y^2 + 4y -28 = 0
(5y+14)(y-2)=0
y = 2 or -14/5
x = 2y+1 = 5 or -23/5
2007-11-21 18:43:39
·
answer #6
·
answered by norman 7
·
0⤊
0⤋
x = 1 + 2y
second equation becomes
(1 + 2y)² + y² = 29
5y² + 4y - 28 = 0
(5y + 14)(y - 2) = 0
y = -14/5 or y = 2
so then
when y = -14/5 then x = -23/5
when y = 2 then x = 5
~~
2007-11-21 18:41:26
·
answer #7
·
answered by ssssh 5
·
0⤊
0⤋
x=1+2y replace to other equation:
(1+2y)^2 + y^2 = 29
5y^2 + 4y - 28 = 0
y=2 or y= -14/5
x=5 x= -23/5
2007-11-21 18:38:19
·
answer #8
·
answered by tinhnghichtlmt 3
·
0⤊
0⤋
put x = 1 + 2y into equation two, we get 5y^2 + 4y - 28 = 0
then we can get ( 5y + 14)(y - 2 ) = 0
so y = - 14/5 or y = 2
2007-11-21 18:41:45
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
set x=2y+1
substitute 2y+1 for x
(2y+1)(2y+1) +y^2=29
use FOIL
4y^2+4y+1+y^2=29
combine like terms, and set equal to '0'
5y^2+4y-28=0
Factor
(5y+14)(y-2)=0
y=2,y=-14/5
I figure you can take it from here
2007-11-21 18:45:51
·
answer #10
·
answered by Steve M 3
·
0⤊
0⤋